The first described male Tube-web Spider for mainland Australia: Ariadna kiwirrkurra sp. nov. (Araneae: Segestriidae) - Baehr, Barbara C.; Whyte, Robert (Zootaxa, 2016)
Males of Ariadna kiwirrkurra sp. nov., collected on the 2015 Bush Blitz biodiscovery expedition to the Kiwirrkurra Indigenous Protected Area (IPA) are the first Segestriid males described for mainland Australia.